Lamb, Coleridge, and the Poetics of Publication. Issue 3 (October 2020) - Howe, Anthony
Abstract : This essay explores the poetics of Lamb's early letters to Coleridge. I argue for a sharp awareness, on Lamb's part, of the potentially negative effect publication can have on literary writing. Lamb resists this at the level of epistolary form, by entwining his sonnets with the letters into which he writes them. Where Lamb's poems, taken in themselves, remain modest performances, the letter-poem hybrid texts in which they participate are of significant critical interest. Among other things they establish a critique of Coleridge and his paying court to the literary marketplace. These insights, I go on to suggest, can also help us to understand both writers' more mature work, notably the complex lyric-epistolary compound that is Coleridge's 'This Lime-Tree Bower My Prison'.